Exploring educational transitions and cultural adaptations: Afghan female undergraduate student’s experiences in transitioning from Afghanistan to Bangladesh - Amani, Sidiqa (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Education degree in Educational Leadership and School Improvement, 2023.